Ways of Psychological Work with Primary Class Students - Abduolimova, Maftunakhon; Mutalibova, Madinakhon (Journal of Innovation in Education and Social Research, 2023)
In this article, the psychology of working with elementary school students of pedagogues is highlighted, the process of acceleration of changes in the psychology of students, the crisis process that occurs at each age period is highlighted. How to work with students during the period of psychological changes in students is covered.